Effects of Melatonin on Anti-oxidative Systems and Photosystem II in Cold-Stressed Rice Seedlings - Han, Qiao-Hong (Front Plant Sci, 2017)
Melatonin (N-acetyl-5-methoxytryptamine) plays important role in multiple plant developmental processes and stress responses. We investigated the possible mediatory role of melatonin in growth, photosynthesis, and the response to cold stress in rice by using three different experiments: soaking seed; immersing roots, and spraying to leaves with 0, 20, or 100 μM melatonin. After 6 days of cold stress, the growth of rice seedlings was significantly inhibited, but this inhibition was alleviated by exogenous melatonin. Furthermore, exogenous melatonin pretreatment alleviated the accumulation of reactive oxygen species, malondialdehyde and cell death induced by cold stress. Melatonin pretreatment also relieved the stress-induced inhibitions to photosynthesis and photosystem II activities. Further investigations showed that, antioxidant enzyme activities and non-enzymatic antioxidant levels were increased by melatonin pretreatments. The treatment methods of seed soaking and root immersion were more effective in improving cold stress resistance than the spraying method. The results also indicated the dose-dependent response of melatonin on rice physiological, biochemical, and photosynthetic parameters.